Polynomial Asymptotics of Entire Functions of Finite Order - Borova, O. I.; Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We obtain new asymptotic relations for entire functions of finite order with zeros on a ray under the condition of regular growth for the counting function of their zeros. These relations improve the well-known results of Valiron.